Staphylococcus aureus nasal carriage before breast reconstruction: antibiotic resistance, biofilm formation, and virulence genes—a single center in vitro observation - Jarzynka, Sylwia; Koryszewska-Bagińska, Anna; Nowikiewicz, Tomasz; Szczepańska, Anna; Olędzka, Gabriela; Szymankiewicz, Maria (Frontiers in Microbiology, 2025)
IntroductionInfections caused by Staphylococcus aureus (S. aureus) in patients undergoing mastectomy followed by breast reconstruction present significant therapeutic challenges. Studies suggest that S. aureus may be transmitted from nasal carriage, potentially leading to postoperative infections. However, knowledge regarding the potential pathogenicity of S. aureus nasal carriage strains in women undergoing breast reconstruction in Poland remains limited. This study aimed to characterize S. aureus isolates obtained from screening nasal swabs.MethodsA total of 33 methicillin-sensitive S. aureus (MSSA) isolates were analyzed. These strains exhibited a high prevalence of genes encoding adhesion and antibiotic resistance. The most frequently detected virulence genes included sarA (100%), an activator of protein A; cna (100%), encoding collagen adhesin; blaZ (100%), associated with β-lactamase production; the icaADBC operon (82–100%), responsible for extracellular polysaccharide synthesis and intracellular adhesion; and bap (36%), encoding a surface-associated biofilm protein.ResultsMost isolates (79–100%) demonstrated a strong capacity for biofilm formation and exopolysaccharide production, confirmed by independent methods. Notably, all strains (100%) remained susceptible to ciprofloxacin at increased exposure levels. RAPD analysis revealed low genetic diversity among the isolates.DiscussionOur findings indicate that S. aureus isolates from nasal carriers undergoing breast implantation exhibit antibiotic resistance, biofilm-forming ability, and harbor multiple virulence genes. Early detection of S. aureus colonization via nasal swab screening may be crucial for managing infection risk in patients undergoing breast reconstruction.